EFEKTIFITAS PROSES BELAJAR MENGAJAR PADA SEKOLAH DASAR NEGERI 13 GUGUS II KECAMATAN PALU SELATAN KOTA PALU - Asni, Asni (Katalogis, 2015)
The research was based on the there is limitednes in learning and teaching process and teachers’ and realization program that influenced toward school effectiveness. This was a descriptive research with qualitative approach and employing effectiveness concept in an organization. The date from receive informans which edefinite olready porposif with method, intervieu and study observation empathy document. There were 7 informants involved consisting of a principle and teachers. The research showed that the principle had run supervision function whereas the teachers functioned as principle staff that run the learning and teaching process in the class olready the run and fine ol trough in limitedness. Besides, the effectiveness of school not yet optimum, was not only influenced by staff leadership, learning process, staff development, the pupose and expectation of the school, school climate, self control and communication and parents invalvement, but also influenced by the availability of facility of facillity and incentive.